Tirer le fil de Ghardaïa - Valette, Eric (Le journal de la recherche, 2024)
Keywords: Architecture – Mzab

Pouillon en Algérie, l'anachronisme dans la modernité - Djermoune, Nadir (El Watan, 2024)
Place: Alger
Keywords: Architecture – Mzab

André Ravéreau, Sub-Saharan Africa works. Transpositions and Synthesis between North and South Sahara - Ruggeri, Daniela (FAMagazine. Ricerche e progetti sull'architettura e la città, 2024)
This paper investigates the Sub-Saharan works of architect André Ravéreau (Limoges 1919-Aubenas 2017), as interpretations of the Modern Movement in Africa. A student of Auguste Perret, Ravéreau was strongly influenced by Le Corbusier, so much so that he followed in his footsteps by making a journey to study the Saharan architecture of the M'Zab Valley, made known to the West thanks to Le Corbusier’s 1931-33 Carnets de voyage. In the 1960s, Ravéreau moved to Algeria, where he worked for about twenty years, holding important positions. From 1965 to 1973 he was Architecte en chef des monuments historiques d'Algérie. From the 1970s onwards, his work took him beyond the Algerian desert, to Sub-Saharan Africa, where he received commissions for school and health buildings in Mali, Mauritania and Burkina Faso; he then took part in the competition for the French Embassy project in Uganda. In his discovery of this “new Africa”, Ravéreau brings with him the experience learned in the M'Zab, which he transfers into his sub-Saharan projects, arriving at new “tropical” solutions always strongly contextualised.
Keywords: Architecture – Mzab

Ahkam : l'autre maison mozabite - Bouali-Messahel, Mounia (Suspended spaces, 2024)
Keywords: Architecture – Mzab

L'architecture du M'Zab - Bendimerad, Sabri; Bouali-Messahel, Mounia (Suspended spaces, 2024)
Keywords: Architecture – Mzab

André Ravéreau, progetti in Africa Subsahariana. Trasposizioni e sintesi tra nord e sud del Sahara - Ruggeri, Daniela (FAMagazine. Ricerche e progetti sull'architettura e la città, 2024)
L’articolo esplora i progetti subsahariani dell’architetto André Ravéreau (Limoges 1919-Aubenas 2017), che costituiscono una delle molte declinazioni del Movimento Moderno in Africa. Allievo di Auguste Perret, Ravéreau fu influenzato anche da Le Corbusier, tanto da ripercorrere le sue tracce compiendo un viaggio per studiare l’architettura sahariana della Valle del M’Zab, resa nota all’occidente dai carnets de voyage di Le Corbu del 1931-33. Negli anni Sessanta Ravéreau si trasferisce in Algeria, dove lavora per circa vent’anni, ricoprendo cariche importanti, dal 1965 al 1973 è Architecte en chef des monuments historiques d’Algérie. A partire dagli anni Settanta il lavoro lo porterà a spingersi in Africa Subsahariana, dove riceve commesse per edifici scolastici e sanitari in Mali, Mauritania e Burkina Faso; partecipa al concorso per il progetto dell’Ambasciata francese in Uganda. Nella scoperta di questa “nuova Africa”, Ravéreau porta con sé l’esperienza appresa nel M’Zab, che trasferisce nei suoi progetti subsahariani, approdando a nuove soluzioni “tropicali” sempre fortemente contestualizzate. , The paper investigates the Sub-Saharan works of architect André Ravéreau (Limoges 1919-Aubenas 2017), as interpretations of the Modern Movement in Africa. A student of Auguste Perret, Ravéreau was strongly influenced by Le Corbusier, so much so that he followed in his footsteps by making a journey to study the Saharan architecture of the M'Zab Valley, made known to the West thanks to Le Corbusier's 1931-33 Carnets de voyge. In the 1960s Ravéreau moved to Algeria, where he worked for about twenty years, holding important positions, from 1965 to 1973 he was Architecte en chef des monuments historiques d'Algérie. From the 1970s onwards, his work took him beyond the Algerian desert, to Sub-Saharan Africa, where he received commissions for school and health buildings in Mali, Mauritania and Burkina Faso; he then took part in the competition for the French Embassy project in Ouganda. In his discovery of this “new Africa”, Ravéreau brings with him the experience learned in the M'Zab, which he transfers into his sub-Saharan projects, arriving at new "tropical" solutions always strongly contextualized.
Keywords: Architecture – Mzab

Understanding the authenticity of traditional housing in Algeria: keys to intervening in heritage spaces of mozabit housing - Moufida, Sebti; Faten, Ghanemi; Djamel, Alkama (Indonesian Journal of Social Science Research, 2024)
The human settlement of M'zab is a traditional habitat located in the Sa-hara of Algeria; it considered by its richness in bioclimatic elements and distinguished by a typological variety. This study aims to discover the traditional habitat in the Sahara of Algeria, by shedding light on the con-structive richness in the habitat of M'zab according to its natural context. We used an analytical approach to examine the fundamental aspects: the natural context, the morphology, housing and the construction. To carry out this study, we carried out numerous field visits, including taking pho-tographs, direct surveys and in-depth discussions with specialists. These initiatives have enriched our understanding of the specificities of the habitat studied. The habitat of M'zab opened the doors to the discovery of traditional habitat in Algeria, which harmonizes perfectly with its cli-matic and natural environment. In addition, it allowed us to understand in more depth the intervention strategies in the heritage areas of the Sa-hara, while drawing valuable lessons from the past.
Keywords: Architecture – Mzab; Urbanisme – Mzab

Towards Sustainable architectural practice in specific contexts Through the lens of Spatial Agency approach: The Tafilelt new Ksar (Algeria) as a case study - Bakour, Fatah; Chougui, Ali (E3S Web of Conferences, 2024)
The emergence of the Spatial Agency approach marks a significant shift from traditional architectural paradigms, emphasizing the interconnectedness of social and technological networks involving diverse stakeholders. This approach aims to reframe conceptual frameworks and establish a resilient built environment. In contrast, the M'Zab architecture in Ghardaïa, Algeria, is adapted to the harsh desert landscape, reflecting socio-cultural identity and meeting the needs of local communities. The ksar of Tafilelt in Ghardaïa exemplifies strategies for preserving M'Zab architecture and urban identity while promoting sustainability and empowering marginalized communities through intricate socio-technical networks. This study examines how architectural interventions in Tafilelt's new ksar, as a system of agency, contribute to social and ecological resilience, health, well-being, and the continuation of Mozabite architectural identity, particularly focusing on its Eco-Parc. The research methodology utilizes the Mapping Controversies technique and Bruno Latour's Actor-Network Theory (ANT) as a conceptual framework. Spatial agency is presented as an innovative strategy fostering socio-ecological networks of resilience in the new ksar of Tafilelt. It views architecture as an ecosystem that balances human agency and non-human local devices, empowering communities in decisionmaking and management. This approach promotes ecological balance, social equity, economic resilience, and health enhancement. The findings and framework can guide local architects in understanding and navigating the complexities of architectural practice, especially in marginalized communities. Future research could explore the application of these concepts in other Algerian regions and compare them with traditional government project approaches to understand their benefits and drawbacks.
Keywords: Architecture – Mzab

AI Expedition: Towards new challenges in built heritage valorization—A case study of the aesthetic experience in the M'zab Valley - Zair, Nourelhouda; Boussora, Kenza (2024)
Situated in the arid landscapes of southern Algeria and Classified as a UNESCO World Heritage in 1982, the ancient cities of the M'zab Valley embody a profound link between architecture, community, and the harsh Saharan milieu. The exploration of such intangible attributes that mirror human experience is necessary in appraising ancient built environments. This study aims to understand the aesthetic experience of the site’s visitors, essential to understand its intangible aspects. Using Natural Language Processing (NLP) a method based on Artificial Intelligence (AI), the research systematically analyzes online reviews, revealing recurring positive keywords like "amazement" and "wonder." The NLP methodology unveils subtle emotional patterns, enriching discussions on cultural heritage preservation. Extracted insights aid in formulating targeted protection plans, aligning conservation efforts with the valley's authentic qualities. This data-centric approach not only enhances preservation effectiveness but also preserves the captivating experiences that contribute to the valley's global significance
Keywords: Architecture – Mzab

Preventive conservation – a means of sustainability of cultural heritage: The case of the M’Zab Valley - Ouaali, Samia; Anouche, Karima (Architecture Papers of the Faculty of Architecture and Design STU, 2024)
The management of heritage sites is fundamental to their conservation and sustainability, and more broadly, it contributes to the preservation of...
Keywords: Architecture – Mzab; Monuments – conservation – Mzab

Étude des matériaux et techniques de réhabilitation de la place du marché de Ghardaïa - Heriz, Ameur; Houdjedje, Hammou (Université de Ghardaia, 2024)
Keywords: Architecture – Mzab

The sustainable potential of the architectural and urban heritage of the Algerian ksour - Souami, Mohamed Adel; Elhaddad, Iheb; Ferhat, Sabrina; Medhouche, Hylda; Mellak, Chamsy; Nebbache, Lynda (Journal of Architectural Conservation, 2024)
This paper aims to assess the sustainability potential of Algerian desert Ksour's architectural and urban heritage. It identifies systems aligning with the 17 sustainable development goals (SDGs), categorized into formal, spatial organization, and architectonic aspects. The approach correlates Ksour's architectural features with SDGs defined by the International Union of Architects, yielding 40 passive features applicable for achieving SDGs. Notably, features like high windows (architectural) and strategic siting (urban) remain relevant for energy efficiency and carbon footprint reduction. This research gives us the opportunity to improve our strategies for rehabilitating and adapting built heritage so that it can meet current environmental challenges, but also opens up the possibility in the future of continuing to identify more sustainable systems by extending the study of heritage examples, but also and above all of developing a reflection on the adaptation of these passive systems in the design of contemporary architectural and urban projects.
_eprint: https://doi.org/10.1080/13556207.2024.2350181
Keywords: Architecture – Mzab

The Social Practices And Their Architectural Reflections On The Dwelling In The M'zab Valley Traditional - Zaaba, Omar; Barkat, Omar (Journal of Namibian Studies : History Politics Culture, 2024)
The traditional architecture in the M'zab Valley was a real response to the needs of the natural community and a direct reflection of its lifestyle, nature of activities, environmental requirements, individual and collective life practices within the intellectual system and its natural framework. Therefore, we do not find any part in this architecture that does not serve a specific function or symbolize a certain goal, considering that all material production in this society is a homogeneous and harmonious expression between needs, aspirations, goals, religious values, organizations and interactive social relationships with nature and climatic factors. Thus, architectural production in general and traditional housing in M'zab specifically testify to all these values and ideas manifested in their patterns, plans, units and architectural elements, It was necessary to study the impact of these social organizations and practices on the traditional dwelling in M'zab, considering it as a fundamental urban unit in shaping its palaces and a real product that reflects the values and ideas of this society. And since the dwelling is part of this human production, its relationship with social practice is a strong and organic relationship.
Keywords: Architecture – Mzab; Irrigation – Mzab; Puits – Mzab

A socio-environmental analysis of contemporary modifications to Algerian Mzab traditional houses - Mouna, Hammou; Drias, Ammar (African Geographical Review, 2024)
Algerian Mzab traditional houses, using passive techniques since the eleventh century (from 1012 to 1882), have seen recent modifications. Analysis of 612 questionnaires and interviews with Mzab residents reveals 81.2% of these houses have been modified. Modifications include adding floors, thinning walls, and replacing lime with cement, driven by the need for space, ventilation, and modernisation. However, such modifications often increase energy consumption, with residents requiring more heating in winter and air conditioning in summer. This reliance on fossil fuels exacerbates regional climate insecurity. Planting roof terraces and using high-insulation building materials can reduce energy consumption in modified Mzab houses.
Keywords: Architecture – Mzab

Habitat vernaculaire saharien et confort thermique : caractéristiques du bâti et modes d’habiter de l’oasis mozabite (Ghardaïa, Algérie) - Bouali-Messahel, Mounia (2024)
ENSA Paris Val de Seine
Keywords: Architecture – Mzab